Pore structure characterization of porous building material by X-ray computed tomography (XCT) and X-ray microscopy (XRM) - Chengnan Shi; Jeroen Soete; Hans Janssen (e-Journal of Nondestructive Testing)
The pore structure of porous building materials, with pore elements ranging from nanometer to millimeter scale, often is a crucial factor that impacts the material’s functional properties. This paper extensively characterizes the pore structure of ceramic brick, a commonly applied porous building material. To address the conflict between the field of view and resolution, an image chain with eight three-dimensional greyscale image sets is acquired through X-ray computed tomography (XCT) and X-ray microscopy (XRM), with their voxel sizes progressively spanning from nanometers to micrometers. The impact of voxel size and sample size on pore structure characterization is examined quantitatively through pore network analysis. After denoising and segmenting the acquired images, the maximal ball method is applied to extract the pore network for evaluation. This paper characterizes the pore structure of ceramic brick through the construction of the image chain. Additionally, scanning the same sample with a finer voxel size naturally captures more details, and allows the pore network extraction algorithm to better preserve pore structure. On the other hand, the impact of sample size on pore network characterization for ceramic brick is negligible if the oversized sample allows sufficient X-ray transmission.